(untitled) (VERITAS LEGIS JOURNAL, 2026)
Traditionally, bank-client relations are considered subject to private (civil) law. However, their legal regulation is characterized by a relatively high level of public law penetration. By applying public law methods of regulation in a number of cases, the state limits freedom of contract and the autonomy of the will of the participants in contractual relations. This raises questions about the scope of such restrictions, the sectoral affiliation of the rules governing bank-client relations, and the methods of their legal regulation. The purpose of this article is to present a legal analysis of the impact of public and private law on bank-client relations. In the course of the research, the authors provide examples of the application of the imperative method in regulating relations between a bank and a client, determine the industry affiliation of the rules governing relations between a bank and a client, and characterize complex banking legal relations, the article compares the influence of public and private law methods of regulation and discusses a comprehensive method of legal regulation of banking relations. The conclusion presents the results of the study.